Do future markets protect the spot markets in developing countries? The case of the Egyptian wheat market - Osama Ahmed (New Medit, 2021)
Egypt is considered a net wheat importer, with the Egyptian market being vulnerable to future wheat markets because of the effect future market price discovery can have on the stability of spot prices. This study assesses the relationship between Egyptian wheat spot prices and future wheat prices in Paris (MATIF) and USA (CBOT). Markov switching-vector error correction methods are used to estimate two regimes by splitting the sample into high and low volatility regimes. This study also examines the dynamic conditional correlation between the prices considered using the asymmetric DCC-GARCH. Results suggest a high volatility regime observed, especially during the extreme market events of the food crisis in 2007-08 and 2010 and following the two revolutions in Egypt in 2011 and 2013 and the time of the economic reform in 2016. This leads to an unstable market and negative impacts on consumers' welfare and food affordability, meaning that futures markets failed to hedge spot wheat market against price volatility. In addition, results from impulse response functions indicate that a 1% shock in futures markets will lead to a positive shock in the wheat spot market, while for the low volatility regime no significant effect.
Keywords: O13; O24; Q13; Q17; 630; DCC-GARCH; food price volatility; future-spot markets; Markov switching; vector error correction